Growth of Trichoderma asperellum with the Addition of Ecoenzyme to Red Glutinous Rice-Based Medium - Khatimah, Husnul; Anhar, Azwir; Advinda, Linda; Farma, Siska Alicia (Jurnal Biologi Tropis, 2024)
Ecoenzyme is a fermented liquid product containing lactic acid bacteria in fruits and vegetables. Nutrients derived from ecoenzymes such as nitrogen are used for growth. This study evaluated the effect of ecoenzyme administration on the number of Trichoderma asperellum spores in brown glutinous rice medium. Trichoderma asperellum is known as a beneficial fungus in the decomposition of solid waste and the enhancement of plant growth. The use of medium made from brown glutinous rice was tested as an alternative to Potato Dextrose Agar (PDA), with the addition of ecoenzyme as an additional nutrient. This study used a Complete Randomized Design (RAL) with six treatments and five repeats. The treatment given is the addition of ecoenzyme concentrations of 0%, 20%, 40%, 60%, 80%, and 100%. Data was analyzed using fingerprints and follow-up tests with DNMRT at an error rate of 5%. Observation of the number of spores is carried out at the age of 60 days by dilution and hemasitometer. The results showed that the 60% ecoenzyme concentration had the highest average spore count and was different from the 0% control. In contrast, the 20% concentration had the lowest average and was the same as the controls. Giving ecoenzyme to brown glutinous rice medium can increase the number of Trichoderma asperellum spores.